Exercício físico resistido em pacientes com doença renal crônica em hemodiálise: ensaio clínico randomizado controlado - Daibem, Celio Guilherme Lombardi [UNESP] (2014)
Patients with chronic kidney disease (CKD) are affected by severe functional limitations, such as low cardiorespiratory fitness, anemia, muscle weakness and malnutrition, which are expressed by pronounced fatigue and physical fatigue, generating high costs to health systems. Consequently a growing number of studies that have used exercise as a complementary therapeutic intervention in dialysis treatment, which describe physiological, functional and psychological improvements of these patients, but there is no consensus on the best type of exercise to be recommended. The aim of this study was to evaluate the effects of 12 weeks of resistance exercise protocol during hemodialysis on functional capacity, respiratory muscle strength, body composition and biochemical variables. The randomized controlled trial was conducted with a sample consisting of 29 patients, divided into control group (GC) (n = 14) and exercise group (GE) (n = 15). Significant differences were observed in the GE for the variables 6MWT - from 528.8 ± 137.8 to 554.5 ± 137.4 meters (p = 0.015); TSL - 12 (2) to 15 (3) repetitions (p = 0.001); MEP - 137 ± 37.1 to 155 ± 52.7 cmH2O (p = 0.031); and Flexibility - 14 (11.3) to 19.9 (11.1) centimetre (p = 0.001). The GE showed a significant increase in total lean body mass (total MM), lower limb lean mass (MM legs) and the sum of lean mass and bone mass (MM + MO), which did not occur with the GC for these variables. Decreased fat mass, total body fat (% of total BF)...